Philosophy of science : a contemporary introduction - Rosenberg, Alex (Routledge, 2012)
Any serious student attempting to better understand the nature, methods and justification of science will value Alex Rosenberg's updated and substantially revised Third Edition of Philosophy of Science: A Contemporary Introduction. Weaving together lucid explanations and clear analyses, the volume is a much-used, thematically oriented introduction to the field.